2014
DOI: 10.1016/j.jtcvs.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ventricular assist device use as a bridge to transplantation does not affect long-term quality of life

Abstract: Over the long term, surviving children who required a long-term VAD as a BTT experience a similar QOL as those who went straight to transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…24 Ezon et al confirmed this finding with a similar study that evaluated patients after HT, looking specifically at patients who had a VAD placed as BTT and again found no difference in QoL following HT when compared with those who did not require MCS. 14 Overall, QoL after pediatric HT is considered good, though studies have noted psychosocial and neurocognitive difficulties in some pediatric patients posttransplant. [25][26][27][28] Perhaps most importantly, in the long term, adult patients who are at least 10 years out from a pediatric HT report no decrease in QoL.…”
Section: Discussionmentioning
confidence: 99%
“…24 Ezon et al confirmed this finding with a similar study that evaluated patients after HT, looking specifically at patients who had a VAD placed as BTT and again found no difference in QoL following HT when compared with those who did not require MCS. 14 Overall, QoL after pediatric HT is considered good, though studies have noted psychosocial and neurocognitive difficulties in some pediatric patients posttransplant. [25][26][27][28] Perhaps most importantly, in the long term, adult patients who are at least 10 years out from a pediatric HT report no decrease in QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experience and coping mechanisms may allow patients to adapt and succeed even though they may still struggle and need support in the process. 34 Very few studies have investigated the impact of peri-operative risk factors on HRQL after pediatric heart transplantation. Our study has identified an association between kidney dysfunction pretransplant and worse HRQL.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important is the long-term effect of MCS on the quality of life in children following transplantation. To date, only two studies have addressed this issue [ 47 , 48 ]. Using a validated generic measure, the Pediatric Quality of Life Inventory, which assesses the quality of life in pediatric heart transplant recipients, has shown that the quality of life of children bridged to transplant with a MCS is not inferior to those who were not bridged with a device.…”
Section: Outcomes After Long-term Vad Supportmentioning
confidence: 99%